Disclosure, Foreign Institutional Investment, and Volatility: A Study in the Indian Context - Bhattacharjee, Titas; De, Suddhasanta (Indian Journal of Finance, 2013)
With global financial integration, emerging markets have gradually become more attractive destinations for international investors who seek higher returns than their own developed markets while diversifying their risk. In India, since the middle of 2003, significant increase in the inflow of foreign institutional investments has made it the most important source of portfolio investment. The Indian business newspapers repeatedly point out that the actions of foreign investors have an impact on the movement of the share prices. However, previous literature (before 2003) on Indian data established that stock returns influence the movement of foreign institutional investment, and not vice versa. However, these studies looked at the period before 2003, and given the structural change in share prices and net foreign institutional investment flows since the middle of 2003, it would be sensible to re-examine their relationship using more recent data. Also, as equity markets gets stuck by weaknesses in transparency and information disclosure policies, its reliability is said to be improved by raising firms' disclosure. Hence, in this present study, using firm-level Indian data from 2001 to 2008, we show that both concurrent and lagged foreign institutional investment flows and voluntary disclosure are negatively related to returns volatility. Our empirical results are consistent with the previous literature. Supporting our speculation that institutions herd on disclosure quality (signals), we tried to find out whether the correlation between volatility and foreign institutional ownership is higher for firms with higher voluntary disclosure. At the end, we tried to find out the direction of relationship among all of these three variables, and attempted to see whether there exists any moderating or mediating effect of one variable over another on volatility. The results are robust to many control variables. We analyzed the annual reports of selected Indian listed companies in constructing firm-specific voluntary disclosure measures and used panel data for regression purposes.